White supremacy, racism and the coloniality of anti-trafficking - Kempadoo, Kamala; Shih, Elena (Routledge, 2023)
"Chapters in this book offer critically valuable scholarship grounded in anti-racist perspectives illuminating the historical and contemporary racial mechanisms within global anti-trafficking discourses and practices. Topics converge and intersect with gender, citizenship, sexuality, class formations, and the global political economy"--